Covid-19 or geographies of inequality? The case of Lisbon metropolitan area and an essay for the future - Santos, Sebastião; Ferreiro, Maria de Fátima (RGS-IBG Annual International Conference, 2022)
The geographic expression of Covid-19 impacts proves that the planet's surface is not the map where everything is equalized, displaying deep social and economic inequalities that have settled in societies and territories. These contrasts are detected at different scales: between geographical North and South, between countries, between regions, or even in metropolitan areas. Having this in mind, the paper presents the territorial inequalities of global events, such as the current pandemic crisis of Covid-19, in the case of Lisbon Metropolitan Area. This goal will be addressed through a methodological approach that considers the multidimensional nature of territory and, therefore, the diversity of responses to this radical event. The analysis will also consider the impact of other global events such as recent economic crisis.